2000
DOI: 10.1126/science.287.5462.2456
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Variations at the Base of the Solar Convection Zone

Abstract: We have detected changes in the rotation of the sun near the base of its convective envelope, including a prominent variation with a period of 1.3 years at low latitudes. Such helioseismic probing of the deep solar interior has been enabled by nearly continuous observation of its oscillation modes with two complementary experiments. Inversion of the global-mode frequency splittings reveals that the largest temporal changes in the angular velocity Omega are of the order of 6 nanohertz and occur above and below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
287
3
13

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(337 citation statements)
references
References 27 publications
34
287
3
13
Order By: Relevance
“…32). The torsional oscillations were first discovered on the Sun's surface [129], and then were found in the upper convection zone by helioseismology [130,131]. The depth of these evolving zonal flows is not yet established.…”
Section: Results For Solar Rotationmentioning
confidence: 99%
“…32). The torsional oscillations were first discovered on the Sun's surface [129], and then were found in the upper convection zone by helioseismology [130,131]. The depth of these evolving zonal flows is not yet established.…”
Section: Results For Solar Rotationmentioning
confidence: 99%
“…The presence of the ∼1.3-year period within the active belt allows the conjecture that the ALs may be connected to a source region close to the tachocline zone. This implication is based on the results by Howe et al (2000), who found the same period of the radial torsional oscillation at the tachocline zone during the period between 1995 and 2000 and by Bigazzi & Ruzmaikin (2004), who argued that the non-axisymmetry of the solar dynamo could only remain at the bottom of the convective zone.…”
Section: Temporal Properties Of Solar Flares Near Almentioning
confidence: 91%
“…The half width of this AL was about 30°, a flip-flop event was identified, but the most interesting result was that the flux emergence exhibited a 1.3-year periodicity within the active longitudinal domain while this period was absent from of this domain. This raised the possible interpretation that the active regions emerging within the AL are anchored at the bottom of the convective zone where this period was also detected by Howe et al (2000) and the rest of the active regions emerge from higher layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Komm et al (2002Komm et al ( , 2003Komm et al ( , 2004 and Howe et al (2000) found out that the 1.3-year periodicity at the base of the convection zone is most pronounced in the solar rotation rate at the equator of the tachocline. The 1.3-year variation of the solar rotation rate in the vicinity of the tachocline was also revealed by Schou (2003).…”
Section: Variation Of Solar Indices With a Period Of 13 Yearsmentioning
confidence: 99%